A comparative study of nebulized versus intravenous lignocaine to suppress the haemodynamic response to endotracheal suction in patients on mechanical ventilation - Agrawal, Akhilesh; Lele, Smita S.; Tendolkar, Bharati A. (International Journal of Research in Medical Sciences, 2017)
Background: Cardiovascular response to tracheal suction is decreased by intravenous lignocaine. Tracheal suction is a powerful stimulus that causes intense haemodynamic changes in patients on mechanical ventilation. In the present study, we compared the effect of nebulized and intravenous lignocaine on haemodynamic response to tracheal suctioning in patients on mechanical ventilation through an endotracheal tube. Methods: A prospective randomized cross over study was conducted in Lokmanya Tilak Municipal Medical College and Government Hospital, Sion, Mumbai, India during the period of January 2012 to September 2013. Sixty patients requiring tracheal suction through an endotracheal tube received 1.5 mg/kg of lignocaine in the nebulized form or as an intravenous injection on two different occasions. Heart rate (HR), mean arterial pressure (MAP), systolic and diastolic blood pressure (SBP and DBP) and peripheral capillary oxygen saturation (SPO2) were recorded at baseline, after the administration of lignocaine, after two successive suctions and once in two minutes for the next 16 minutes Results: In the present study, SPO2 decreased in response to ETT suctioning in both the study groups as compared to the pre-suctioning value. However the changes in the SPO2 were not significant when compared between the groups. Changes in HR, SBP, DBP and MAP were not significantly different between the two routes of lignocaine administration. Conclusions: From the present study, we can conclude that the abolition of haemodynamic response to tracheal suction is similar with both intravenous and nebulized lignocaine. But the return of MAP towards baseline value was observed to be earlier with nebulized lignocaine than with intravenous lignocaine which favours use of nebulized lignocaine over intravenous lignocaine. With built-in nebulizer facility in the current intensive care ventilators, this technique should be easy, more effective and assure better haemodynamic stability than intravenous lignocaine during tracheal suction.